Prognostic significance of pulsatile tinnitus in cervical artery dissection - Kellert, Lars; Kloss, Manja; Grond-Ginsbach, Caspar (European journal of neurology, 2016)
Background and purpose: Our aim was to investigate whether pulsatile tinnitus (PT) in cervical artery dissection (CeAD) has prognostic significance. Methods: All CeAD patients from the CADISP (Cervical Artery Dissection and Ischemic Stroke Patients) study with documentation of PT were analysed. The presence of PT was systematically assessed using a standardized questionnaire. Stroke severity at admission was defined according to the National Institutes of Health Stroke Scale (NIHSS). Excellent outcome after 3 months was defined as a modified Rankin Scale of 0-1. Results: Sixty-three of 778 patients (8.1%) reported PT. PT+ patients presented less often with ischaemic stroke (41.3% vs. 63.9%, P < 0.001), more often with dissection in the internal carotid artery (85.7% vs. 64.2%, P = 0.001), less often with vessel occlusion (19.0% vs. 34.1%, P = 0.017) and more often with excellent outcome at 3 months (92.1% vs. 75.4%, P = 0.002). Logistic regression analysis identified PT as an independent predictor of excellent outcome after 3 months [odds ratio (OR) 3.96, 95% confidence interval (CI) 1.22-12.87] adjusted to significant outcome predictors NIHSS on admission (OR 0.82, 95% CI 0.79-0.86), Horner syndrome (OR 1.95, 95% CI 1.16-3.29) and vessel occlusion (OR 0.62, 95% CI 0.40-0.94) and to non-significant predictors age, sex, pain and location of CeAD. Conclusion: The presence of PT in CeAD is associated with a benign clinical course and predicts a favourable outcome.